Serum Vitamin-D Levels And Severity Of Clinical Depression In Patients Of A Psychiatric Clinic in Pakistan: Serum Vitamin-D Levels and Severity of Clinical Depression - Ul Haq, Mian Mukhtar; Ul Haq, Mian Ayaz; Durrani, Talha; Humayun, Omama; Ullah, Imran; Durrani, Daniyal (Pakistan Journal of Health Sciences, 2022)
Vitamin D deficiency is often correlated with nervous system disorders like major depression, Parkinson’s disease and dementia. While much of the clinical literature suggests its association with clinical depression, very few studies have looked into the relationship between vitamin D levels and clinical depression severity. Objectives: To find out the association between vitamin D levels in patients suffering from different severities of clinical depression with the confounding socio-cultural factors of a third-world country i.e., Pakistan. Methods: The cross-sectional study was conducted in Lady Reading Hospital, Peshawar for five months with convenience sampling. Results: Overall, the study had 132 (36.57%) males and 229 (63.43%) females, and 236 diagnosed cases of Clinical Depression. In terms of Vitamin D levels, 242 (67.04%) had deficient, while 77 (21.33%) and 42 (11.63%) had insufficient and normal vitamin D levels, respectively. There was a statistically significant difference in the serum Vitamin D levels between at least two groups (F (3,232) = [38.64], p < 0.05). Conclusions: Vitamin D levels showed a dose-dependent, inverse relation with the severity of clinical depression in the Pakistani population